Exploring ornamental plants for birds in Forest Research Institute Malaysia, Kepong urban forest setting / Sabrina Idilfitri - Idilfitri, Sabrina (2014)
Urban drift or urbanisation leads to maximum impact in human daily activities that entirely changes rural landscape into urban style. It also led to an increasing stress (social aspect) and living costs (economic aspect) and invasion of exotic species (environmental stress) into the living environment. This research aim is to study the contribution of ornamental plants as food plants and shelter for birds in urban forest parks. The objectives are 1) to explore the perception by various professionals on their understanding on the contribution of urban parks, ornamental plants and birds in urban area about conserving birds in urban forest parks; 2.a) to identify the native and exotic plant species as food plants and shelter for common resident birds in urban forest park and 2.b) to compare the efficiency of native and exotic plants as food plants and shelter; and 3) to develop guidelines on the selection of ornamental plants as food plants and shelter in urban forest park for urban birds. This research will conduct using the combination of questionnaire survey and observation, which comprise of academicians and professionals. The findings stated that the most significant plants category as food plants for birds are fruit and flowering trees, attract insects and should be native species. Meanwhile, the findings on plants’ observation indicate that native plant species provide the most nutritious and all year-round food resources according to the frequency of plant parts (attract insects, fruits, grains and nectars) and a better shelter for bird species based on the physical characteristics (multi-stem plants, dense canopy and evergreen).